Peran Penting Rekam Medis Elektronik Dalam Transformasi Digital Di Puskesmas Tabunganen - Asih, Hastin Atas; Indrayadi, Indrayadi; Auliani, Firda; Istiqamah, Nur (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
This community service aims to enhance the knowledge of medical record officers regarding electronic medical records. Electronic medical records have been adopted in community health centers as a technological innovation to optimize public health services. A profound understanding of EHR by medical record officers is crucial in improving the efficiency and effectiveness of health services. Community health centers face the risk of lagging behind in EHR implementation due to their large scale and small number. This community service provides a positive contribution in preparing Tabunganen Community Health Center to implement electronic medical records.